Implementasi Manajemen Risiko dalam Meningkatkan Keberlanjutan Bisnis - Handayani, Agustuti; Irsandi; Hawazien; Khorunnisa (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2024)
This study aims to analyze the implementation of risk management in improving business sustainability in Micro, Small, and Medium Enterprises (MSMEs) in Bandar Lampung. A qualitative-descriptive approach was used to explore the understanding, practices, and obstacles faced by MSME actors in risk management. Data were collected through in-depth interviews, direct observation, and document analysis in MSMEs from various business sectors.The results of the study indicate that the implementation of risk management, such as product diversification, financial management, and the use of digital technology, have a positive impact on income stability, operational efficiency, and customer trust. However, the level of risk management implementation among MSMEs still varies. The main obstacles include limited resources, lack of knowledge about risk management, and minimal access to training or mentoring programs.This study concludes that risk management plays an important role in supporting the sustainability of MSME businesses by mitigating challenges and opening up opportunities for innovation. To optimize the implementation of risk management, collaborative support is needed between the government, business actors, and other related parties in providing relevant policies, training, and access to technology. Keywords: risk management, business sustainability, MSMEs, Bandar Lampung, digital technology.